Druga Godisnja izlozba : Centra z savremenu umetnost - Beograd. - Fund for an Open Society - Centre for Contemporary Art, Belgrade (Beograd : Fund for an Open Society - Center for Contemporary Art, 1997)
Andelkovic, Dejan ; Apsolutno ; Bajic, Mrdan ; BOR, Yane Zivadinovic ; Davic,Aleksandar ; Duric, Uros ; Glid, Gabriel ;Ilic, Ivan ; Jelenkovic, Dragan ; Krgovic, Dobrivoje ; Mgolombane, Samuel ; Milivojevic, Era ; Munisic, Mirjana ; Naskovski, Zoran ; Neskovic, Predrag ; Papic, Dragan ; Prodanovic, Mileta ; Radovanovic, Jelica ; Rajcevic, Simonida ; RTTM, p. ; Srdic, Dragan ; Todosijevic, Rasa Dragoljub ; Tomic, Milica
Druga Godisnja izlozba : Centra z savremenu umetnost - Beograd / 2nd Annual Exhibition of Centre for Contemporary Art - Belgrade, April 1997
boek